PERLINDUNGAN HAK ANAK DALAM PENELITIAN DIGITAL : TINJAUAN SISTEMATIS TERHADAP KERANGKA ETIKA DAN PEDOMAN - Naidasari, Ulfi; Waliah, Diyah Rutin; Mas’ula, Siti; Arifin, Slamet (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to identify and analyze ethical frameworks involving the protection of children’s rights in digital educational research, and to compare them with traditional research methods. Using a Systematic Literature Review (SLR) approach, the study explored empirical and theoretical literature related to the ethics of children’s digital education, with a focus on privacy, informed consent, and potential exploitation associated with digital technologies. Data were collected through systematic literature searches in Google Scholar and Scopus databases, followed by article selection using strict inclusion and exclusion criteria. Data analysis was conducted through thematic synthesis and quality appraisal of relevant studies. The findings show that although efforts have been made to develop strong ethical frameworks, significant gaps remain in their implementation, particularly in inadequate privacy policies and child protection within EdTech platforms. Participatory approaches in research are increasingly valued; however, traditional methods often limit the depth of data obtained. The study also highlights challenges posed by artificial intelligence, including algorithmic bias, privacy concerns, and reduced human oversight. In conclusion, the study recommends the development of more ethical AI design focusing on transparency, fairness, and stronger child participation as active agents in digital education ecosystems. It also emphasizes the need for policymakers and educators to adopt more inclusive, child-rights-based approaches in digital educational research and technology development.